Long COVID-19 autoantibodies and their potential effect on fertility - Talamini, Laura; Fonseca, Dennyson Leandro M.; Kanduc, Darja; Chaloin, Olivier; Verdot, Cindy; Galmiche, Christian; Dotan, Arad; Filgueiras, Igor Salerno; Borghi, Maria Orietta; Meroni, Pier Luigi; Gavrilova, Natalia Y.; Ryabkova, Varvara A.; et al. (Frontiers in Immunology, 2025)
Impaired spermatogenesis has been reported in coronavirus disease 2019 (COVID-19) patients. However, the impact of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on male fertility remains unclear. The purpose of this multicenter study was to investigate the possible impact of SARS-CoV-2 infection on male fertility and determine the potential reasons leading to impaired male reproductive functions. In silico approach identified 60 amino acid sequences containing at least five continuous residues shared by SARS-CoV-2 Spike glycoprotein and spermatogenesis-linked proteins. Four synthetic peptides were tested with sera from independent cohorts of patients with acute and long COVID-19 syndrome (LCS), and naïve vaccinated subjects. Immunogenicity and pathogenicity studies were performed by immunizing mice with two selected peptides and testing the antigenicity of induced antibodies. While none of four peptides were recognized by antibodies from vaccinated people, infected patients exhibited high reactivity to peptide 4, and LCS patients, especially women, showed elevated antibody levels against peptide 2. Women with LCS and chronic fatigue syndrome had higher levels of peptide 2–reacting antibodies than those with idiopathic chronic fatigue syndrome. Noteworthy, peptide 2 antibodies showed, in in vitro experiment, a specific interaction with mouse testicular tissue antigens. These findings raise the possibility that cross-reactive epitopes between SARS-CoV-2 Spike protein and spermatogenesis-related antigens may affect infected patients’ fertility, suggesting a potential for autoimmune responses with human consequences.